A goal-aligned coordinate system for invasion games - Brandes, U. (Journal of Sports Analytics, 2023)
Spatial locations of players and game devices are a fundamental data type in team-sports analytics. They are typically specified in Cartesian coordinates, but with varying conventions for the origin, orientation, and scaling. In invasion games such as football, basketball, or hockey, however, many markings are of fixed dimension even when the field of play is not, so that the game-specific meaning of locations does not scale uniformly. We propose an alternative coordinate system that accommodates variable field sizes by using the goals instead of a corner or the center of the field of play as frames of reference.